Effectiveness Study of Twin Tunnel Nanjung in Flood Management of Citarum River - Sindy Witari; Rakhmat Yusuf (Universitas Negeri Semarang, 2025)
Indonesia has a high risk of natural disasters such as flooding, which particularly affects the West Java region. Floods often occur due to high flow rates that exceed the capacity of water bodies, triggered by rainfall and population growth. Based on the data collected, floods hit Dayeuhkolot, Bojongsoang and Baleendah Subdistricts with water levels between 40 - 200 cm which resulted in 919 households with 3,577 people displaced. Flood control can basically be done in various ways, but it needs to consider the whole system and find the most optimal one. To reduce flooding around the Upper Citarum, the Nanjung Twin Tunnels were built. Therefore, researchers are interested in further reviewing the performance and effectiveness of the Nanjung Twin Tunnel for the handling of the Upper Citarum. This research uses descriptive method with HEC-RAS v6.5 software modeling approach with 2D method. From the modeling results, it was found that after the installation of Twin Tunnel Nanjung, the flood inundation area was reduced by 64% from 13.44 km2 to 4.8 km2 and the depth was reduced by 2-3 m on average at 5 points in Dayeuhkolot area.